2021
DOI: 10.3389/fpubh.2021.720787
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Trends and Research Hotspots in Disaster Epidemiology From 1985 to 2020: A Bibliometric Analysis

Abstract: Background: Disaster epidemiology has not attracted enough attention in the past few decades and still faces significant challenges. This study aimed to systematically analyze the evolving trends and research hotspots in disaster epidemiology and provide insights into disaster epidemiology.Methods: We searched the Scopus and Web of Science Core Collection (WoSCC) databases between 1985 and 2020 to identify relevant literature on disaster epidemiology. The retrieval strategies were TITLE-ABS-KEY (disaster epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“… 25 , 26 Second, because of the continuous updating of data in the WoSCC database, the bibliometric analysis results typically fall behind the actual research situation. 27 , 28 Finally, the newly published and potentially influential publications may not have been included in our study due to low citation frequency. Therefore, the understanding and scientific trends of esketamine research may change with time and bibliometric data updates.…”
Section: Limitationsmentioning
confidence: 99%
“… 25 , 26 Second, because of the continuous updating of data in the WoSCC database, the bibliometric analysis results typically fall behind the actual research situation. 27 , 28 Finally, the newly published and potentially influential publications may not have been included in our study due to low citation frequency. Therefore, the understanding and scientific trends of esketamine research may change with time and bibliometric data updates.…”
Section: Limitationsmentioning
confidence: 99%
“…Another considerable part focused on the impact of the pandemic from the point of view of business or the economy. Of these 489 reviews, 17 included some reference to stress [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ] but none mentioned burnout. Likewise, 5 considered teachers [ 71 , 76 , 77 , 78 ], with 3 of them focusing on university teachers [ 71 , 77 , 78 , 79 , 80 ] and the other 2 on the use of learning through ICT [ 77 , 80 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress has shed light on the prevalence and significance of tumors in disaster-affected populations (11). Studies have shown that disasters can increase the incidence and prevalence of tumors due to factors such as exposure to carcinogenic substances and stress (12).…”
Section: Prevalence and Significance Of Tumors In Disaster-affected P...mentioning
confidence: 99%